(untitled) (E Conference Zone, 2025)
The article conducts an in-depth examination of the legal status of civil servants in developed countries. It delves into the legislative frameworks that regulate the rights, obligations, responsibilities, restrictions, and social guarantees of civil servants. Through the analysis of legal systems in the USA, Japan, Germany, the UK, and other nations, the study identifies distinctive characteristics and shared principles of civil servants’ legal status. The main objective is to propose effective legal reforms to improve Uzbekistan’s civil service system by drawing on the practices of developed nations.